Stream Morphometry as Response to the Level of Tectonic Deformation on Sorowako and Surrounding Areas, Indonesia - Sambodo, Tri Hananto; Sukiyah, Emi; Hutabarat, Johanes (UIR PRESS, 2025)
Sorowako and surrounding areas are geologically influenced by Sulawesi’s microcontinent movement, which has produced several geological phenomena. Morphometry is one of the parameter that can reveal geological condition of particular area. Morphometric analysis of water catchment area in Sorowako and surrounding areas using Bifurcation Ratio (Rb) and Drainage Density (Dd) can provide comprehensive information on level of deformation in Sorowako region. Analysis result of Bifurcation Ratio Index (Rb) on water catchment area reveals that Rb<3 value is dominant and equally spread in Sorowako region, it varies from 0.094 to 2.888. However in several place the value of Bifurcation Ratio (Rb) index is more than 5 (Rb>5) with varies from 5.142 to 10.250. Drainage Density (Dd) value ranges from 0.907 to 8.422 with an average value is 4.125 describes impact of erosion and tectonic on Sorowako region. Based on morphometric analysis of two parameters, Sorowako and surroundings area have been heavily impacted by tectonic activity on Sulawesi island. In western, eastern and northern regions on water catchment area, level of deformation tends to be higher compared to southern region. This can be seen on analysis result of water catchment area 43, water catchment area 196, and water catchment area 302 that have relatively larger number of stream orders, and also have Bifurcation Ratio’s value less than three (Rb<3). Information of tectonic deformation level on Sorowako region through morphometric analysis is important to further use as a basis for water catchment area management planning, so that it can identify areas prone to geological disasters. This fairly high level of tectonic deformation also believed to be a controlling factor for nickel grade contained in Sorowako and surrounding areas which allow supergene enrichment to occurs in rocks.